Implementasi Metode Weighted Product Pada Sistem Pendukung Keputusan Pemilihan Karyawan Terbaik - Alvian, Muhammad Christian; Pratama, Dicky (MDP Student Conference, 2025)
PT. Badak Prima Lestari is a company engaged in the business of heavy equipment (Heavy Equiqment) and lifting equipment (Material Handling Equitments) in Indonesia. PT. Badak Prima Lestari was established in 2021, although PT. Badak Prima Lestari already has a mature recruitment procedure, there are still shortcomings in the system that can support decisions in selecting the best employees. Especially the determination in assessing employee performance and determining the best employees can be aspects that need to be improved because the existing criteria are ineffective. With this research which aims to develop a decision support system (DSS) using the Weighted Product (WP) method to facilitate the assessment process. This application is made website-based using the laravel framework with the rational unified process (RUP) system development method. The results obtained are that the system can help companies to increase assessment efficiency automatically, provide measurable weights, transparently, the system developed meets the research objectives.